Accelerating Global Economic Recovery and Building Resilient Economies in the Post-COVID-19 Era - Chirwa, Mululu (Journal of Applied Business and Economics, 2023)
World economic trends in recent times have been grossly influenced by the ramifications of COVID-19. The paper endeavours to assess the severity of world economic downturn due to the COVID-19 pandemic of 2019-2021 relative to the global recession of 2008-2010. It also attempts to surface emerging trends for accelerating economic recovery while building resilience. It employed desk review with a mixed approach. The sample size spanned the 4 main international economies and 21 representative countries. A One-Paired 2 Sample means t-Test at  0.05, 1-tail, 8 df shows that, the economic collapse experienced due to the pandemic was just as bad as that of the 2008-2010 economic recession. Monitoring database reveals that low income and emerging markets are recovering faster than advanced economies from the shocks of the pandemic. Meanwhile, the t-Test  0.05, 1-tail, 8 df again shows that, the world economy is steadily recovering. The recovery can be accelerated and made resilient through economic restructuring by integrating emerging trends such as AI, technology, education and greening into economies.